Korelasi Komitmen, Kompetensi Profesional, Dan Motivasi Berprestasi Terhadap Produktivitas Kerja Guru SMK Negeri Di Kota Arga Makmur - rasyid, Hendy; Nur Sasongko , Rambat; Putri Kartiwi, Asti (Manajer Pendididikan, 2025)
This study examines the correlation of commitment, professional competence, and achievement motivation to the work productivity of teachers at state vocational schools in the city of Arga Makmur. The productivity of school organizations is largely influenced by teacher work productivity. Teacher work productivity should be an important concern because high and low teacher work productivity can affect the achievement of overall school organizational goals. Using a descriptive correlational quantitative approach, data were collected through surveys, documentation, and questionnaires with teachers at State Vocational Schools in Arga Makmur City, then analyzed using correlation techniques. The results showed a positive and significant correlation between commitment, professional competence, and achievement motivation to work productivity. In addition, the four variables together contribute significantly to teacher work productivity. This study emphasizes the importance of maintaining and improving commitment, professional competence, and achievement motivation to work productivity. The findings provide insights for principals, teachers, and aspiring educators.